CRIMINALIZATION OF TEACHER DISCIPLINARY ACTIONS: A JURIDICAL ANALYSIS OF THE CONFLICT BETWEEN CHILD PROTECTION AND PEDAGOGICAL AUTHORITY - Harmono Harmono (Hukum Responsif, 2027)
Background. The phenomenon of increasing teacher reporting by students' parents due to the imposition of disciplinary sanctions shows that there is a change in relations in the world of education that has an impact on the legal position of teachers. Disciplinary actions that are actually part of the pedagogical process are often questioned as a violation of the law, thus leading to a tendency to criminalize. Aims. This study aims to analyze the legal limitations of teacher disciplinary actions from a positive legal perspective, examine the criminalization practices that occur, and formulate a proportionate legal protection model. Methods. The method used is normative-juridical, with legislative, conceptual, and case approaches. Data were obtained through literature studies of primary and secondary legal materials and were then analyzed qualitatively using a prescriptive approach. Result. The results of the study show that there is no clear boundary between disciplinary action and violence in positive law, thus creating legal uncertainty. In practice, it is found that there is a tendency to use criminal law excessively for pedagogical actions without considering the context and educational purpose. Conclusion. This research offers a legal protection model based on the principle of proportionality, a restorative justice approach, standardization of disciplinary actions, and limited immunity for teachers who act in good faith. This model is expected to strike a balance between protecting children's rights and protecting the teaching profession. Implication. This condition has implications for the weakening of teachers' authority and the emergence of concerns in carrying out educational functions.